Arraying Autoantibodies in SLE – Lessons Learned - Wang, L.; Mohan, C.; Li, Q.-Z. (Current Molecular Medicine, 2015)
Systemic lupus erythematosus (SLE) is a chronic autoimmune connective tissue disease characterized by the production of a large number of autoantibodies, but the etiology is complex and poorly understood. A range of different platforms have served as screening methods for the determination of autoantibody specificities over the past few decades. Proteomic microarray is a relatively new high-throughput technology which is playing an increasingly important role in autoantibody diagnostics. In this article, we review different platforms for assaying autoantibodies in SLE, and highlight the use of autoantigen arrays as powerful tools for autoantibody exploration in SLE.
Keywords: autoantibody profiling